Rebuilding with PAMPERO of destructive hypersonic tests on honeycomb sandwich panels in the T-117 wind tunnel. Issue 2 (June 2020) - Annaloro, J.; Ledermann, V.; Constant, E.; Spel, M.; Vasse, C.; Rivola, V.; Drozdov, S.M.; Omaly, P.
Abstract: CNES develops its spacecraft-oriented tool named PAMPERO since 2013. PAMPERO aims to simulate the complete atmospheric reentry of a spacecraft including the fragmentation and ablation processes. One of its objectives is to provide a support to experts using current certification tools such as DEBRISK, in which the user needs to pre-fragment the space vehicle. The purpose of this paper is to describe the rebuilding of two destructive tests of aluminium honeycomb sandwich panels performed at TsAGI. A detailed analysis of modelling simplifications of honeycomb structures is presented.